Association of ischaemic stroke subtype with long‐term cardiovascular events. (2nd April 2014) - Ntaios, G.; Papavasileiou, V.; Makaritsis, K.; Milionis, H.; Michel, P.; Vemmos, K.
<x xml:space="preserve">Abstract</x> Background and purpose There is no strong evidence that all ischaemic stroke types are associated with high cardiovascular risk. Our aim was to investigate whether all ischaemic stroke types are associated with high cardiovascular risk. Methods All consecutive patients with ischaemic stroke registered in the Athens Stroke Registry between 1 January 1993 and 31 December 2010 were categorized according to the TOAST classification and were followed up for up to 10 years. Outcomes assessed were cardiovascular and all‐cause mortality, myocardial infarction, stroke recurrence, and a composite cardiovascular outcome consisting of myocardial infarction, angina pectoris, acute heart failure, sudden cardiac death, stroke recurrence and aortic aneurysm rupture. The Kaplan–Meier product limit method was used to estimate the probability of each end‐point in each patient group. Cox proportional hazards models were used to determine the independent covariates of each end‐point. Results Two thousand seven hundred and thirty patients were followed up for 48.1 ± 41.9 months. The cumulative probabilities of 10‐year cardiovascular mortality in patients with cardioembolic stroke [46.6%, 95% confidence interval (CI) 40.6–52.8], lacunar stroke (22.1%, 95% CI 16.2–28.0) or undetermined stroke (35.2%, 95% CI 27.8–42.6) were either similar to or higher than those of patients with large‐artery atherosclerotic stroke (LAA) (28.7%, 95% CI 22.4–35.0). Compared with LAA, all other TOAST types had a higher probability of 10‐year stroke recurrence. In Cox proportional hazards analysis, compared with patients with LAA, patients with any other stroke type were associated with similar or higher risk for the outcomes of overall mortality, cardiovascular mortality, stroke recurrence and composite cardiovascular outcome. Conclusions Large‐artery atherosclerotic stroke and cardioembolic stroke are associated with the highest risk for future cardiovascular events, with the latter carrying at least as high a risk as LAA stroke.